Relationship of Pruritus with Biochemical and Haematological Parameters in Haemodialysis Patients (A Single Center Study). - Ghassan, Ban; Jaffar Alalsaidissa, Jaffar N.; Hashim Al-Saedi, Ali J.; Alawchi, Sabah N. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Pruritus often constitutes a major problem for patients with end stage renal disease. The pathophysiological mechanism of chronic kidney disease -associated pruritus is poorly defined.Objectives: To evaluate the prevalence of uremic pruritus in dialysis patients and their correlation with the laboratory and clinical parameters in some Iraqi patients with chronic renal disease.Patients & methods: This analytic, descriptive, cross-sectional study was performed on 103 patients on haemodialysis. Blood urea, creatinine, calcium, phosphorus, alkaline phosphatase and parathyroid hormone were determined. Complete blood count was also performed.Results: Of the 103 patients included in the study the, 79 patients (76.7%) had pruritus of whom, 27 (34.1%) had mild pruritus, 30 (38%) had moderate and 22 (27.9%) had severe pruritus. No significant association (p> 0.05) was found between pruritus and each of age and haemodialysis duration. There was no significant difference (p > 0.05) in the urea, creatinine, calcium, phosphorus, alkaline phosphatase, parathyroid hormone, hemoglobin, hematocrit, white blood cells, neutrophils, eoisinophils, basophils mean values among patients who had no pruritus, mild, moderate and severe pruritus. A significant positive correlation (p > 0.05) was found between severity of pruritus in pruritic patients and each of age, hemoglobin and hematocrit levels.Conclusion: Our study showed that age, hemoglobin and hematocrit levels had a significant positive correlation with the severity of pruritus in pruritic patients.